The global death and disability burden associated with a high BMI in children and adolescents, 1990–2019 - Song, Ying; Zhou, Yuan; Feng, Xiaojin; Fu, Jieting; Liu, Yongping (Frontiers in Endocrinology, 2024)
Objective: Exploring changing trends of burden caused by overweight and obesity among children and adolescents from 1990 to 2019 in the global, regional, and national levels, based on data from the Global Burden of Disease study (GBD) 2019.Annual number and rate of deaths and disability-adjusted life years (DALYs) associated with high BMI among children and adolescents at global, regional and national levels by age groups, sexes and sociodemographic index (SDI) from 1990 to 2019 were collected from GBD 2019. Change percentage of numbers, and estimated annual percentage changes (EAPCs) of rates were calculated to determine the temporal trends.Results: From 1990 to 2019, the global high BMI-related deaths decreased by 34%, but DALYs increased by 48%. Death rates in females were higher than in males, although both shown decreased trends. For DLAYs rate, both sexes shown increasing trends, but rate in males has surpassed that in females since 1999. High BMI had the greatest impact on children under 5 years, while the burden in other age groups continued to rise. Regionally, High-income Asia Pacific experienced the fastest decrease of deaths rate (EAPC= -9.57), and East Asia saw the fastest increase of DALYs rate (EAPC= 3.47). Globally, as age increases, the proportion of disease burden attributed to high BMI in females generally increase.Our findings emphasize the urgent need to improve prevention efforts for overweight and obesity among children and adolescents.